A hybrid CFD RANS/Lagrangian approach to model atmospheric dispersion of pollutants in complex urban geometries. (11th April 2019) - Bahlali, Meissam L.; Dupont, Eric; Carissimo, Bertrand
Lagrangian atmospheric dispersion models consist of tracking the trajectories of particles of pollutant emitted into the atmosphere. In this paper, the objective is to compare the Lagrangian and Eulerian dispersion models in the same computational fluid dynamics code ( Code Saturne ), therefore using the same wind and turbulence fields for both. The Lagrangian stochastic model used in this work is the simplified Langevin model (SLM) of Pope (1985, 2000) and pertains to the approaches referred to as probability density function methods. This model has been extensively used in turbulent combustion or multiphase flows, but to our knowledge, it has not been used in atmospheric dispersion applications. First, we show that the SLM respects the well-mixed criterion. Then, we validate the model in the case of a continuous point release with uniform mean wind speed and turbulent diffusivity. Finally, we validate the model with an experimental campaign involving a stably stratified surface layer.